Effect of replacing milk products with a soybean protein isolate milk replacer in diets for nursery pigs - D B Jones; D F Li; Jim L Nelssen; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1989)
One hundred eighty pigs (21 d of age and averaging 14.5 lb) were used to determine if a milk replacer containing soybean protein isolate can replace dried skim milk and dried whey in a high nutrient density starter diet. Pigs received pelleted feeds that were: 1) corn-soybean meal control; 2) a high nutrient density diet (HNDD) containing 20% dried skim milk and 20% dried whey; 3 and 4) diet 2 with milk rcplacer substituted for 50% and 100% of the milk products; 5) corn-milk replacer; 6) corn-milk products. Average daily gain (ADG), average daily feed intake (ADFI), feed conversion (F/G), and fecal scores were determined on d 7, 14, and 35 of the experiment. Apparent digestibilities of nitrogen and dry matter were determined on d 14. On d 7, pigs fed the corn-soybean meal control had the poorest performance. Feed efficiency was better for pigs fed the corn-milk replacer and corn-milk products diets than for pigs fed the HNDD's. At d 14, ADFI was less for pigs fed the corn-milk replacer and corn-milk products diets than for pigs given the HNDD's. Digestibilities of nitrogen and dry matter were greater for all diets vs the control, and there was decreased incidence of diarrhea as the level of milk replacer increased in the diet. At d 35, ADG was greatest for pigs given the HNDD's and ADFI was lower for pigs fed the corn-milk replacer and corn-milk products diets. Our results indicate that milk replacers containing a high quality soybean protein isolate can be substituted for milk products in HNDD's with no reduction in pig performance.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Soybean protein isolate; Dried skim milk; Dried whey; Nursery pigs